Theoretical Approach to Training and Work Motivation in Relation to Employee Performance at the Panwascam Agency Soreang District Bandung Regency - N R Muslim; D A Wahab Sya’roni (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Efficient and responsive employee performance is very important for every agency, especially government agencies, both individually and in related groups in election supervision. The method used is descriptive qualitative method. The purpose of this study was to determine the relationship between the theoretical approach to the effect of training and work motivation in relation to employee performance. This research will be carried out within the scope of the Panwascam secretariat in Soreang District, Bandung Regency, the objects of this research include the chairman, commissioners and members. This research will be reviewed based on previous research which states that the influence of training and motivation greatly influences employee performance. The research method uses a qualitative descriptive method that refers to the sources of interviews and observations as well as literature studies by studying reference books and previous studies. The results of this study indicate that the variables of the influence of training and motivation on employee performance are both very influential. The results of the interview show that between the two variables used to determine the magnitude of the influence on employee performance, the motivation variable has the greatest influence on increasing employee performance at the Panwascam secretariat, Soreang District, Bandung Regency